2023
DOI: 10.1002/ppul.26437
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for invasive home mechanical ventilation duration in bronchopulmonary dysplasia

Abstract: Background: Children with bronchopulmonary dysplasia (BPD) who require invasive home mechanical ventilation (IHMV) are medically vulnerable and experience high caregiving and healthcare costs. Predictors for duration of IHMV in children with BPD remain unclear, which can make prognostication and decision-making challenging.Methods: A retrospective cohort study of children with BPD requiring IHMV was conducted from independent children's hospital records (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This is especially important given research showing that children from racial/ethnic minority backgrounds or lower income experienced disproportionately longer time using IHMV and tracheostomies. 39,40 Our results also provided key information on core functionality that would be needed when designing an RPM approach for this population, including: (1) supporting multiple caregivers and nurse logins, (2) reminders to users such as texts or other phone notifications, and (3) individualized data programming based on ventilation settings, schedules, and child activity. This latter finding is consistent with previous literature noting that the care needs of children using IHMV are highly variable between patients and for a…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is especially important given research showing that children from racial/ethnic minority backgrounds or lower income experienced disproportionately longer time using IHMV and tracheostomies. 39,40 Our results also provided key information on core functionality that would be needed when designing an RPM approach for this population, including: (1) supporting multiple caregivers and nurse logins, (2) reminders to users such as texts or other phone notifications, and (3) individualized data programming based on ventilation settings, schedules, and child activity. This latter finding is consistent with previous literature noting that the care needs of children using IHMV are highly variable between patients and for a…”
Section: Discussionmentioning
confidence: 87%
“…To prevent any potential for further disparities in care or health outcomes, RPM system designs must consider alternative pathways for those with barriers to digital technologies. This is especially important given research showing that children from racial/ethnic minority backgrounds or lower income experienced disproportionately longer time using IHMV and tracheostomies 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study of children with BPD requiring IHMV in New Zealand during 2005−2021 revealed that half of the patients were weaned off HMV by 36 months and 90% by 52 months once home. This was longer in the patients with higher discharge age corrected for tracheostomy (DACT; chronological age at discharge minus age at tracheostomy) 23 …”
Section: Factors Affected the Successful Weaningmentioning
confidence: 99%